STUDI KESESUAIAN ANTARA KURIKULUM SPEKTRUM 2008 SMK TEKNIK PEMESINAN DENGAN KEBUTUHAN KOMPETENSI DI BENGKEL PEMESINAN DI SURAKARTA - Wahnuri, Wahyu (Jurnal Nosel, 2014)
The objective of this research was to determine the suitability between spectrum curriculum 2008 SMK machinery engineering and competency needed on production engineering workshop in Surakarta. This research belonging to evaluation research used descriptive qualitative research study. The result of this study are : (1) competency profile of production machine operators in production engineering workshop at Surakarta are varieties, from the results of the study can be concluded that the design of DKK and KK Mechanical Machining Skills Competency declared to represent the competencies needed to become a production machine operator. There are several additional competencies that are considered by the industry namely includes personal competence discipline, work ethic, work spirit, enthusiasm for learning, honest, never give up, responsibility, and competence in the field of machining itself. (2) Mapping the suitability of basic competence DKK and KK Competency of Technical Skills Machining with competence profile of production machine operators in production engineering workshop Surakarta declared appropriate. With namely details of DKK Competency Technical Skills Machining declared low of 40.10%, and KK Mechanical Machining Skills Competency declared quite high at 60.72%.